CHEMICAL AND IMMUNOLOGICAL QUALITY OF COLOSTRUM: EFFECT OF BREED AND DURATION OF MILKING - kumar, Harish (Indian Journal of Dairy Science, 2014)
The objective of the present investigation was to compare the chemical and immunological quality of crossbreed goats, Sannen x Beetal and Alpine x Beetal and to study the effect of duration of milking. Fifteen Sannen x Beetal and Alpine x Beetal dairy goats were selected for the study and colostrum samples were collected at an interval of 12 h from 0 to 72 h after kidding. The colostrum was analyzed for pH, total solid, fat, protein, lactose, ash, and IgG content. The levels of protein and total IgG dropped quickly from the time of birth till72 h postpartum in both the breeds. The colostrum constituents viz. protein, total solids and ash were significantly higher (P< 0.05) at0 h and then decreased sharply, whereas lactose content was found to be directly proportional to the duration of milking. Despite the similar trends of increase and decrease in the constituents of colostrum in both the breeds, various significances of statistical differences with respect to the constituents were observed between the breeds.